PHOSPHATE MINERALOGY OF NYF-TYPE GRANITIC PEGMATITES - Nizamoff J.W.; Falster A.U.; Simmons W.B. (My University, 2002)
Presents an abstract of the article 'Phosphate Mineralogy of NYF-Type Granitic Pegmatites,' by J.W. Nizamoff, A.U. Falster, W.B. Simmons and K.L. Webber presented at the 28th Rochester Mineralogical Symposium.
Keywords: MINERALOGY